The factors affecting stunting among toddlers in Ende, Indonesia - Sisilia Leny Cahyani; Theresia Avila Kurnia; Maria Salestina Sekunda; Aris Wawomeo; Pius Kopong Tokan; Yustina P.M. Paschalia; Anatolia K. Doondori; Irwan Budiana; Martina Bedho; Yoseph Woge; Raimunda Woga; Marieta K.S. Bai; Khrispina Owa (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: Short stature in toddlers indicates chronic nutritional problems that are influenced by maternal conditions, birth weight, toddler weight, and infant diseases or other problems that indirectly affect health.Purpose: To determine the factors affecting stunting among toddlers in Ende, IndonesiaMethod: Correlational using a cross sectional approach to 155 toddlers. Purposive sampling was used to collect samples from eight sub-districts in Ende Regency. Questionnaires were distributed for data collection. In this study, bivariate analysis used chi-square test, and multivariate analysis used logistic regression.Results: Univariate analysis showed that most of the respondents (mothers of toddlers) had a history of short stature, was not at risk for gestational age, had poor nutrition, had a good level of knowledge about infant food and nutrition, had no history of infection during pregnancy, and always had antenatal care check-ups. Factors under five identified that almost all have a history of infectious diseases, have been sick in the last month, have no history of low birth weight, have complete vaccination, are not premature, and have intrauterine growth, and growth restriction. Environmental factors indicate that some respondents have clean latrines, have a distance to health facilities <1 km, have clean drinking water, and are not pregnant and breastfeeding.Conclusion: Several variables have a significant relationship with stunting in such as exclusive breastfeeding, infectious diseases, drinking water quality, and distance to health facilities. The results of the multivariate analysis showed that the infectious disease variable was the dominant variable causing stunting in Ende Regency.Suggestion: Local health authority to garner cooperation from various regional bureaucracies in Ende Regency to tackle stunting in this area.